3D Digital Survey of Iron Tie-Rods in Masonry Buildings: Cross-Sections Analysis and Error Estimation. Issue 3 (3rd April 2019) - Battini, Carlo; Calderini, Chiara; Vecchiattini, Rita
ABSTRACT: Ancient iron tie-rods are handcrafted elements with large geometric irregularities, due to production techniques (they are shaped by hammering and linked by hot-forging) and corrosion processes. In common practice, their cross section (that is one of the main parameter to assess their strength) is manually measured on site with a manual caliber. By analyzing a set of detailed three-dimensional (3D) digital surveys of real ancient tie-rods, this study provide an evaluation of the errors made by in-situ manual geometric measurements. In particular, it shows that, in some cases, manual on-site survey is sufficiently reliable and has errors that fall below 10%. Moreover, it shows that when tie-rods have high corrosion levels in hidden zones (typically those close or within the retaining walls) the on-site survey of visible parts only may produce far greater errors that exceed 100%, leading to a strong overestimation of the cross-section of the tie. The ongoing study is a first step toward the definition of correction coefficients to be applied to the on-site manual measurements of ancient tie-rods, with the final aim to improve the reliability of structural analyses.